Yanzhou Coal Mining Company Limited. Overseas acquisitions (B) - McFarlan, F. Warren (Franklin Warren); Jin, Yongjun; Li, Xiaohui ([London] : SAGE, 2016)
When applying for its wholly-owned subsidiary Yancoal Australia to acquire Felix Resources Limited in 2009, Yanzhou Coal made several promises to the Australian Treasury to ensure approval of the acquisition. Zhang Baocai, a board member of Yanzhou Coal and one of the chief acquisition negotiators, clearly remembers how Yanzhou Coal fulfilled its promises one by one after the acquisition in 2009.
Originally Published in: McFarlan, F. W., Jin, Y., & Li, X. (2013). Yanzhou Coal Mining Company Limited: Overseas Acquisitions. 0-413-322. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Yanzhou Coal Mining Company Limited (Firm); Consolidation and merger of corporations -- China -- Case studies; Consolidation and merger of corporations -- Australia -- Case studies; International business enterprises -- Case studies